Influence of kenaf fibre orientation effect on the mechanical properties of hybrid structure of fibre metal laminate - Ng, Lin Feng; Dhar Malingam, Sivakumar; Zakaria, Kamarul Ariffin; Bapokutty, Omar; Subramonian, Sivarao (University Putra Malaysia Press, 2017)
Efforts to reduce manufacturing cost and negative environmental impacts have seen the mixture of natural fibre with synthetic fibre in composite structures. However, there are limited studies on the notch effect and fibre orientation on mechanical properties of hybrid fibre metal laminate (FML). In this study, tensile properties of FML with notch and different fibre orientation were investigated. The hybrid FML incorporated with kenaf fibre at the middle layer was compared with FML with three layers of E-glass fibre. Kenaf fibre and E-glass fibre used were in plain woven form. The FML in 2/1 configuration was manufactured through hot press manufacturing method to bond layers of annealed aluminium 5052 to the composite. Tensile test was conducted in a quasi-static manner according to ASTM E8. The results showed FML with three layers of glass fibre exhibited higher tensile strength compared with hybrid FML. However, the introduction of kenaf fibre in hybrid FML reduces the notch and fibre orientation sensitivity compared with glass fibre reinforced FML.